(untitled) (Universal International Scientific Journal, 2026)
This thesis develops the theoretical and methodological foundations for the formation of convergent competence in future teachers and proposes a pedagogical model aimed at its implementation. The study extensively examines the need to elevate teacher professional training to a new level within the modern educational system, where the importance of interdisciplinary integration, problem-based thinking, and reflective practice is steadily increasing. In the thesis, convergent competence is interpreted as the ability to integrate pedagogical, psychological, and methodological knowledge, to make innovative and well-grounded decisions in complex pedagogical situations, and to conduct systematic analysis of professional activity.